VECM Model Analysis of Carbon Emissions, GDP, and International Crude Oil Prices - Xiaohua Zou (Discrete Dynamics in Nature and Society)
As a kind of scarce natural capital, energy makes more and more obvious constraint effects on economic growth. And energy consumption is the major source of greenhouse gas emissions. This brings about the problems of the relationships among energy consumption, carbon emissions, and economic growth, which is worthy of long-term attention. This paper attempted to explore the interactive relations among American oil prices, carbon emissions, and GDP through the data analysis from 1983 to 2013. This paper adopted time series vector error correction model (VECM) approach to conduct stationarity test, cointegration test, stability test, and Granger causality test. The results indicated that, no matter in the short term or long term, oil price fluctuation is the reason why carbon emissions change, while the GDP fluctuation is not the reason for the growth of carbon emissions. The oil price impacts will have a great influence on GDP and carbon emissions in the short term, but, the in long term, the influence will tend to be gentle.